Leaf lipid degradation in soils and surface sediments: A litterbag experiment. (February 2017) - Nguyen Tu, Thanh Thuy; Egasse, Céline; Anquetil, Christelle; Zanetti, Florent; Zeller, Bernd; Huon, Sylvain; Derenne, Sylvie
Graphical abstract: Highlights: Biomarker content varied substantially in soil and at water-sediment interface. Almost all lipids were still present after 2 yr degradation but had different decay profiles. Although fatty lipid content decreased to < 10% after 2 yr, main distribution pattern remained unchanged. Abstract: The fate of leaf lipids upon early diagenesis was monitored in a two year litterbag experiment in a soil and at the water-sediment interface of an adjacent pond. The biomarker content of degrading leaves exhibited substantial variability among litterbags, even for a given time step within a given environmental condition, likely reflecting natural microenvironmental variability. Due to this variability and the oxic conditions in the pond, no substantial difference between the soil and the pond could be evidenced in the biomarker degradation pattern. An occasional increase in the abundance of several biomarkers (β- sitosterol, oleanolic acid, C16 phytyl ester, C27 n -alkane) was also noted during the experiment, which was attributed to release of bound compounds and/or an external contribution. Nevertheless, absolute quantification showed that the concentration of all lipid constituents was reduced, but they exhibited different decay profiles: (i) rapid extensive degradation (phytyl ester), (ii) exponential-like decrease (fatty lipids) and (iii) variable degradation profile (polycyclic triterpenoids). However, all the main constituents initially present in the senescent leaves were still detected after two years of degradation in both environments. Fatty lipids abundances generally decreased to < 10% of the initial content but the main distribution features (carbon number maximum and predominance) remained unchanged. The results thus tend to validate their use as proxy for source and environment in ancient organic matter. They also suggest that, on a mid-term basis, a plant biomarker signature is not substantially affected by differential degradation in soil and at the water-sediment interface, at least for a qualitative approach.